PENGARUH PROGRAM PEMUTIHAN PAJAK, PEMBEBASAN BEA BALIK NAMA, DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI UPTB PENGELOLAAN PENDAPATAN DAERAH KABUPATEN OKU (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2021)
The purpose of this research is to examine the influence of Tax Exemption Program, Title Transfer Fees Exemption, and Tax Socialization on Motor Vehicle Taxpayer Compliance. The research method used is a quantitative approach. The sample selection used a random sampling method by distributing questionnaires to 100 motor vehicle taxpayers registered at the Office of UPTB Regional Revenue Management in OKU Regency. The analytical method used is multiple linear regression analysis using the IBM SPSS 25 program. Partially the tax exemption program and tax socialization have a significant influence on motor vehicle taxpayer compliance, and Title Transfer Fees Exemption does not have a significant influence. The results of the research simultaneously show that the tax exemption program, Title Transfer Fees Exemption, and tax socialization have a significant effect on the motor vehicle taxpayers compliance at UPTB Regional Revenue Management in OKU Regency.